Analysis of the Development of Human Resource Management Functions (An Analysis of Qur’anic Verses on Human Resource Management) - Uswah Hasanah; Mutiah Khaira Sitohang; M. Iqbal (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Human resource issues are still a highlight and priority for an organization or company to survive and develop in the current era of globalization. The existence of human resources is a determining factor in the successful implementation of an effective organization. Company activities will not be completed properly without being supported by the potential and effective and efficient performance of its human resources. To achieve this success, the existence of human resource management is an absolute thing that must be done optimally so that the purpose of the organization can be achieved. This research aims to examine further the function of human resource management in general, as well as compare it with Islamic rules regarding human resource management contained in the Qur’an so that it can add to the development of human resource management functions both in general and when associated with human resource management in Islam which views humans as having 2 functions, namely as servants and caliphs on earth. This research on Human Resource Management is also the result of the author's observations of human resource management when viewed from an Islamic perspective. This writing is to answer the question of how the human resource management system is viewed from an Islamic point of view. This research method is library research and is included in the category of qualitative research. With thematic method (maudu’iy), namely collecting and analyzing the verses of the Qur'an that talk about the function of human resource management. The results showed that many verses of the Qur'an that examine human resources can be used for the development of human resource management functions and add contributions to the development of Sharia human resource management functions. This research can be continued by studying and deepening the verses of the Koran in subsequent studies so that Islamic human resources have specific advantages.